Genes of the de novo and Salvage Biosynthesis Pathways of Vitamin B6 are Regulated under Oxidative Stress in the Plant Pathogen Rhizoctonia solani - Samsatly, Jamil; Chamoun, Rony; Gluck-Thaler, Emile; Jabaji, Suha (Frontiers in Microbiology, 2016)
B6 is recognized as an important cofactor required for numerous metabolic enzymes, and has been shown to act as an antioxidant and play a role in stress responses. It can be synthesized through two different routes: salvage and de novo pathways. However, little is known about the possible function of the vitamin B6 pathways in the fungal plant pathogen Rhizoctonia solani. Using genome walking, the de novo biosynthetic pathway genes; RsolPDX1 and RsolPDX2 and the salvage biosynthetic pathway gene, RsolPLR were sequenced. The predicted amino acid sequences of the three genes had high degree of similarity to other fungal PDX1, PDX2, and PLR proteins and are closely related to other R. solani anastomosis groups. We also examined their regulation when subjected to ROS stress inducers, the superoxide generator paraquat, or H2O2, and compared it to the well-known antioxidant genes, catalase and glutathione-S-transferase (GST). The genes were differentially regulated with substantial transcript levels as high as 33 fold depending on the gene and type of stress reflecting that differences in the type of damage induced by ROS. Exogenous addition of the vitamers PN or PLP in culture medium significantly induced the transcription of the vitamin B6 de novo encoding genes as early as 0.5 hour post treatment (HPT). On the other hand, transcription of RsolPLR was vitamer-specific; a down regulation upon supplementation of PN and upregualtion with PLP. Our results suggest that accumulation of ROS in R. solani mycelia was linked to transcriptional regulation of the three genes and R. solani vitamin B6 biosynthesis machinery could be implicated similar to catalases and GST as an antioxidant stress protector against oxidative stress.